ARTISTIC AND AESTHETIC PREFERENCES OF ADOLESCENTS IN UKRAINE AND POLAND - Mazur, Piotr; Kondur, Oksana; Budnyk, Olena; Nikolaesku, Inna; Parkulab, Oksana; Lazarovych, Nadiia; Grebeniuk, Nataliya (Revista Inclusiones, 2020)
The urgency of the problem of developing artistic and aesthetic abilities of students in the era of globalization and digital technologies is substantiated in the article. The influence of the educational and mental environment of the country on the development of aesthetic interests of students is characterized. Methods of research: survey (N = 269), methods of pedagogical statistics. The adolescents from Ukraine and Poland on their aesthetic preferences in the proposed categories were involved in the study: choreography, cinematography, theatrical and variety-circus art, literature, song art, drawing and painting, activity in different musical subcultures (emo, hippie, rock, rap etc.), photography (selfie), etc. It was found that the priority aesthetic interests among Ukrainian and Polish students are the following types of art: song art, different types of musical subculture, literature. Adolescents are much less interested in museum art, art photography, theater and fine arts. It was confirmed that the cultural and aesthetic preferences of the respondents are related to various currents and performers of contemporary music, collecting, videos, as well as media (social networking, virtual dating, games, etc.). It was found that gender stereotypes do not have a significant impact on Ukrainian and Polish students in their attitude to art. Usually these artistic and aesthetic interests are similar, which are confirmed by the results of correlation analysis. Emphasis is placed on the need to strengthen the aesthetic orientation of the content of school education for the development of aesthetic culture in students, improving methods and forms of organizing aesthetic development classes in educational establishments of various types, implementation of innovative educational strategies for holistic artistic and aesthetic perception of reality by adolescents.